Preparation, structure, and property of wood flour incorporated polypropylene composites prepared by a solid‐state mechanochemical method. Issue 10 (17th November 2015) - Niu, Zhihai; Chen, Yinghong; Feng, Jiabing
ABSTRACT: In this article, a solid‐state mechanochemical method based on a pan‐mill equipment was used to prepare 60 wt % loading of wood flour (WF) incorporated polypropylene (PP) wood–plastic composite (WPC) with good comprehensive performance. The particle size distribution, crystallization, microstructure, and properties of the prepared WPC were accordingly investigated. The results show that under co‐effects of the strong shear force field of pan milling and the compatibilization of PP grafted maleic anhydride (PP‐g‐MAH), the mixture of PP and WF is effectively pulverized and homogeneously mixed. Meanwhile, the WF particles are adequately activated by exposure of their characteristic functional groups, which is beneficial to the interfacial mechanochemical reaction. PP‐g‐MAH and PP prove to be in situ grafted onto WF particles surface during pan milling, thus resulting in the substantial enhancement in both the dispersion of the added WF fillers in PP matrix and the interfacial bonding. The mechanochemical effects of pan milling could also remarkably promote the heterogeneous nucleation effect of WF particles on PP crystallization and influence the dynamic mechanical behavior of composite. Compared with the unmilled and uncompatibilized composite, the milled and compatibilized WPC material possesses greatly enhanced mechanical performance and shows good application prospects. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43108. Abstract :